Implementation of Three-Dimensional Modeling & Layout in the Animation Rindu Tanah Asal - Fazril, Muhammad; Fris Okta Falma (The Future of Education Journal, 2025)
In the 3D animation production process, modeling and layout serve as the fundamental basis for creating a visual narrative that supports the storyline. This final project, titled "Rindu Tanah Asal", focuses on the development of 3D assets and layout design without covering animation or sound effects. The story portrays the journey of a migrant named Fazril, who longs for his hometown and faces various challenges along the way. The modeling process involves building characters, buildings, and trees using Blender software. The layout is arranged based on the storyboard to maintain visual continuity of the story. This project employs the Multimedia Development Life Cycle (MDLC) method as a framework to ensure a systematic production workflow. The final output consists of 3D assets and layouts ready to be used in the animation phase.